Eco-toxic effects of sulfadiazine sodium, sulfamonomethoxine sodium and enrofloxacin on wheat, Chinese cabbage and tomato - Jin, Caixia (Ecotoxicology (London, England), 2009)
Investigation of the toxic effects of three veterinary drugs [sulfadiazine sodium (SDS), sulfamonomethoxine sodium (SMMS), and enrofloxacin (EFLX)] on seed germination, root elongation and shoot elongation of wheat (Triticum aestivum L.), Chinese cabbage (Brassica campestris L.) and tomato (Cyphomandra betacea) was carried out. Significant linear relationships between the root and shoot elongation and the concentration of veterinary drugs addition were observed. The effects of the three veterinary drugs on seed germination of wheat, Chinese cabbages and tomato were not significant (P > 0.05), but on shoot and root elongation they were markedly significant (P < 0.05). The inhibitory rates of veterinary drugs on root and shoot elongation of crops were significantly stronger than that on seed germination. Based on IC(50) (drugs concentration when 50% plants show inhibition) of root elongation, wheat was the most sensitive plant to the toxicity of SDS with a IC(50) value as high as 28.1 mg/kg; Chinese cabbage was the most sensitive plant to the toxicity of SMMS with a IC(50) value as high as 27.1 mg/kg; tomato was the most sensitive plant to the toxicity of EFLX with a IC(50) value as high as 125.7 mg/kg. The toxic effects of sulfadiazine sodium and sulfamonometh-oxine sodium on the three crops were much higher than that of enrofloxacin